Group Exhibition-Exterritory Project, Initiated and curated by Ruti Sela and Maayan Amir took place in the Mediterranean Sea - Antoniou, Klitsa (My University, 2026)
Exterritory Project, Initiated and curated by Ruti Sela and Maayan Amir took place in the Mediterranean Sea, June 17-21, 2010 Cyprus participation curated by klitsa Antoniou